PERFORMANCE OF SERVICES, COMPANY IMAGES AND LOYALTY OF CUSTOMERS IN THE VILLAGE CREDIT INSTITUTE (LPD) - Arsana, I Komang; Suardhika, I Nengah; Yuesti, Anik (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze customer loyalty due to service performance and corporate image in this case the Village Credit Institution (LPD). Customer loyalty is important for LPD. LPDs are owned by indigenous village communities and for indigenous village communities. This research was conducted in Kesiman LPD with a sample of• The research data were analyzed using SEM PLS. The results showed that service performance has a positive effect on customer satisfaction, company image has a positive effect on customer satisfaction, service performance has a positive effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty company image has a positive effect on customer loyalty. Service performance will be able to influence customer loyalty mediated by customer satisfaction, this means that excellent service performance will increase customer satisfaction so that greater loyalty. Company image will be able to influence customer loyalty which is mediated by customer satisfaction, this means that a very popular company image will increase customer satisfaction so that loyalty is greater.